Online shopping: your rights as a consumer - Amin, Naemah (MACFEA, 2015)
Online shopping has become a trend and manifestation of modern consumer life style in recent years. Despite the advantages, many consumers are not aware of the potential hazards of online shopping. The consumers really need to take extra precaution before participating in any online transactions. They should at least be equipped with basic knowledge of their rights as online shoppers. This piece provides a brief description of the legal protection accorded under Malaysian law to online consumers often known as e-consumers.